2019
DOI: 10.1001/jamaoncol.2019.1449
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab After Completion of Locally Ablative Therapy for Oligometastatic Non–Small Cell Lung Cancer

Abstract: IMPORTANCE Patients with oligometastatic non-small cell lung cancer (NSCLC) may benefit from locally ablative therapy (LAT) such as surgery or stereotactic radiotherapy. Prior studies were conducted before the advent of immunotherapy, and a strong biological rationale for the use of immunotherapy exists in a minimal residual disease state.OBJECTIVE To evaluate whether the addition of pembrolizumab after LAT improves outcomes for patients with oligometastatic NSCLC. DESIGN, SETTING, AND PARTICIPANTSThis single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
197
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(207 citation statements)
references
References 29 publications
7
197
0
3
Order By: Relevance
“…With the development of novel biomarkers, targeted therapies, and immuno-oncologic agents, LAT, including SABR and ablative hypofractionated radiotherapy, will be an attractive new treatment strategy for oligometastatic NSCLC in the near future. Bauml et al [55] ≤4 N/A LAT for all known disease sites followed by pembrolizumab treatment for 6 or 12 months 1-year PFS rate post-LAT, 64%; 1-year OS rate post-LAT, 90.9% PEMBRO-RT [56] N/A N/A SABR to single tumor site followed by pembrolizumab versus pembrolizumab alone…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of novel biomarkers, targeted therapies, and immuno-oncologic agents, LAT, including SABR and ablative hypofractionated radiotherapy, will be an attractive new treatment strategy for oligometastatic NSCLC in the near future. Bauml et al [55] ≤4 N/A LAT for all known disease sites followed by pembrolizumab treatment for 6 or 12 months 1-year PFS rate post-LAT, 64%; 1-year OS rate post-LAT, 90.9% PEMBRO-RT [56] N/A N/A SABR to single tumor site followed by pembrolizumab versus pembrolizumab alone…”
Section: Resultsmentioning
confidence: 99%
“…A recent single-arm phase II study evaluated LAT combined with pembrolizumab treatment targeting PD-1 in patients with NSCLC with ≤4 metastatic lesions [55]. After performing LAT to all known sites of disease, pembrolizumab was administered for 6 months and continued to 12 months in the absence of disease progression or untoward toxic effects.…”
Section: Radiotherapy With Immune Checkpoint Blockadementioning
confidence: 99%
“…The maximum number of metastases ranged from 1 to 8 in 21 selected articles [2]. Additionally, the definition of sOM-NSCLC in prospective clinical trials is also heterogeneous and vary between 1 and 6 [2][3][4][5]. Further, 74-100% of 1211 included in the systematic review patients had ≤2 metastatic sites.…”
Section: Tablementioning
confidence: 99%
“…Therefore, as described in EORTC articles [2,5], 18 FDG-PET-CT, brain MRI-scan and a possible pathological proof of a metastasis are necessary. The promising data about immunotherapy and radiation combination are inspiring new sOM-NSCLC trials, investigating the association of these treatments [3]. Hence, a single definition and recommended staging work-up are crucial.…”
Section: Tablementioning
confidence: 99%
“…Lastly, immunotherapy maintenance after immunogenic interventions such as local ablative therapy or radiation therapy has been shown to be bene cial. For instance, patients with non-small cell lung (NSCLC) cancer treated with maintenance pembrolizumab after ablative therapy on a phase 2 study demonstrated statistically signi cant improvement in progression free survival (PFS) compared to historic controls 25 . In another report by Bersanelli et al 26 , patients who revived concurrent immunotherapy with radiotherapy had a longer PFS compared to patients who received radiation alone.…”
Section: Rationale For Immunotherapy and Platinum-sensitized Radiothementioning
confidence: 99%